2014
DOI: 10.17221/44/2014-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Tensile strength and cellulose content of Persian ironwood (Parrotia persica) roots as bioengineering material

Abstract: Unstable slopes create numerous problems for forest management and may destroy the road network and disturb access to forest. Soil bioengineering is a solution that can prevent these problems and reinforce the hillslope. Persian ironwood is considered as a good protective species for hillslope stability in Iran with an extensive lack of information about biotechnical properties. In this research the root strength of this species and also the relation between root diameter and cellulose content were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The findings are congruent with many other studies (Bischetti et al, 2005;Genet et al, 2005;De Baets et al, 2007;Normaniza et al, 2011;Nyambane et al, 2011;Abdi et al, 2014;Mohammed and Normaniza, 2014;Capilleri et al, 2016). Root chemical components, such as cellulose, lignin, hemicellulose and holocellulose, are closely related to root mechanical properties.…”
Section: Discussionsupporting
confidence: 90%
“…The findings are congruent with many other studies (Bischetti et al, 2005;Genet et al, 2005;De Baets et al, 2007;Normaniza et al, 2011;Nyambane et al, 2011;Abdi et al, 2014;Mohammed and Normaniza, 2014;Capilleri et al, 2016). Root chemical components, such as cellulose, lignin, hemicellulose and holocellulose, are closely related to root mechanical properties.…”
Section: Discussionsupporting
confidence: 90%
“…The scientific community invested some efforts in investigating what factor affects the tensile resistance and, especially, the tensile strength vs. root diameter relationships. Among these factors, there are plant/tree species (Abdi, Deljouei 2019), root age (Loades et al 2013), tree age (Genet et al 2008), root length (Zhang et al 2012), trunk diameter (Deljouei et al 2018), cellulose content (Abdi et al 2014), root moisture content (Yang et al 2016), root dehydration (Boldrin et al 2018), testing season (Makarova et al 1998), living or decaying roots (Schmidt et al 2001), lignin content (Hathaway, Penny 1975), microfibril angle (Kerstens et al 2001), altitude (Genet et al 2011), convergent/divergent topography (Hales et al 2009), soil moisture content (Hales, Miniat 2017), slope gradient (Sun et al 2008) and uphill/downhill position (Abdi et al 2010). Conversely, nobody attempted to explain the variability of elastic modulus, despite the importance of this biomechanical feature as an input parameter in root reinforcement modelling.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical properties of roots are well-known by root maximum tensile force and stiffness. Several researchers indicated that different parameters affect root resistance, including species , root size and age (Loades et al 2013;Gilardelli et al 2017;Boldrin et al 2017), tree age (Genet et al 2008), root length (Zhang et al 2012), DBH (Deljouei et al 2018), cellulose and lignin content (Hales et al 2009;Abdi et al 2014), root moisture content (Moresi et al 2019), root dehydration (Ekeoma et al 2021), season (Makarova et al 1998;, living or decaying roots (Vergani et al 2014), altitude (Genet et al 2011), slope position (Stokes 2002;Abdi et al 2010a), soil moisture content (Tsige et al 2020), and elastic modulus as a root reinforcement input parameter (Cislaghi 2021).…”
Section: Root Reinforcementmentioning
confidence: 99%